All hail chaos - Brennan, Sarah Rees (Brennan, Sarah Rees Time of iron, 2026)
All Hail Chaos is Sarah Rees Brennan's wicked, unmissable sequel to Long Live Evil ("delicious, subversive" -Leigh Bardugo), one of the New York Times "Best Science Fiction and Fantasy of 2024." THE EMPEROR IS HERE. AND SHE MADE HIM WORSE. Rae is a fantasy reader who's been transported to her favorite fictional world of swords and sorcery, castles and monsters. Playing the villainess, she thought she could change the narrative, but this version of the plot is far more deadly than the one she knew. Her friends are on the run: the Cobra shelters in an eerie manor haunted by dark secrets, while Emer and Lia stoke a revolution in the gutters. Undead armies roam the kingdom, raiders camp at the city gates, and the all-powerful Emperor - Rae's favorite character ever, now possibly the greatest monster in the land - wants her to be his evil queen. Romantic in fiction, complicated in reality. What's a villainess to do? Time for wicked bargains and fake engagements, in a fantasy where the most dangerous thing you can do is believe in someone.